The review of the monograph: "Dzamikhov K.F., Kazharov A.G. Kabardino-Balkaria – a Republic within the Russian Federation (1922-2022). – Nalchik: print center publishing house, 2022. – 716 s." - Elena G. Muratova (Кавказология, 2022)
The review on the book “Kabardino-Balkaria as a Republic within the Russian Federation (1922-2022)” prepared and published by doctors of historical sciences, professors K.F. Dzamihov and A.G. Kazharov is devoted to the subject that became repeatedly the subject of study of native historians and lawyers. In the contemporary socio-political discourse of life of the peoples of our region, the theme under study saves its relevance. The preparation and publication of a fundamental work devoted to the 100th anniversary of Kabardino-Balkaria makes it possible to consider that the authors could provide a strictly academic and scientifically grounded analysis of the historical preconditions and various stages in the formation of national autonomy of the peoples of KBR. All the sections of the publication proposed by the authors have scientific content and “carry great educational and upbringing potential”. The publication deserves the highest praise and undoubtedly contains a merging potential in the modern socio-political and spiritual life of Kabardino-Balkar society.